Pengaruh Kecerdasan Emosional Dan Motivasi Belajar Terhadap Prestasi Belajar Dengan Tingkat Pemahaman Akuntansi Sebagai Variabel Intervening - Tri Indro Afianty Benu; Paskah Ika Nugroho (Universitas Pendidikan Ganesha, 2021)
This research was conducted to find out how in the influence of emotional intelligence and learning motivation on learning achievement with the level of understanding of accounting as an intervening variable. In this study the type of data used is primary data, data obtained using a questionnaire as a research instrument which is then distributed to 75 respondents. In this case the respondents are accounting student class of 2017, 2018, and 2019, Faculty of Economics and Business, Satya Wacana Christian University. This research uses quantitative methods in the form of survey. The results obtained from this emotional intelligence has a negative effect on learning achievement, emotional intelligence has a positive influence on the level of accounting understanding, learning motivation has a positive influence on learning achievement, learning motivation has a positive influence on the level of accounting understanding, the level of accounting understanding has a negative effect on learning achievement, learning motivation has a negative influence on learning achievement with the level of understanding accounting as an intervening variable, emotional intelligence has a negative effect on learning achievement with the level of understanding accounting as an intervening variable.